Evaluation of anaerobic digestates from sewage sludge as a potential solution for improvement of soil fertility. (November 2019) - Cristina, Giulio; Camelin, Enrico; Pugliese, Massimo; Tommasi, Tonia; Fino, Debora
Highlights: Anaerobic digestates from sewage sludge (SSADs) were characterised. SSADs revealed an appreciable nutrients content. No phytotoxic effects were observed at low digestate concentrations. Plant growth significantly improved after amendment with SSADs. SSADs fertilizing effect was more consistent on a nutrient poor soil. Abstract: Sewage sludge production in European countries has widely raised in the last decade and its fate is currently landfilling, incinerators, composting or land application. To explore its agronomic potential, the main target of this work is to understand the effects of anaerobic digestates from sewage sludge (SSAD). To this aim, four different SSADs (two liquids and two dewatered) were characterized. On the liquid ones, Germination Index was evaluated through a plate bioassay with Lepidium sativum L. seeds; low concentrations of SSAD (2.5%) improved GI in one case, while at higher concentrations phytotoxic effects occurred in both. Then, pot experiments were set in climate chamber with Cucumis sativus L. grown for 30 days on two different substrates: a sandy, alkaline and poor soil, and peat substrate. All SSADs and a mineral fertilizer were used at three increasing dosages: 85, 170, 255 kg of nitrogen per hectare (kg N/ha). Results in terms of germination, dry biomass, chlorophyll content, net photosynthesis, stomatal conductance, CO2 concentration in substomatal cavity and root development were compared to a not treated control. All treatments gave results significantly higher or similar to control on all the parameters evaluated. Moreover, the intermediate nitrogen dosage (170 kg N/ha) generally showed the highest results compared to other dosages, especially for dewatered SSADs. All these results were much more evident for cucumber plants grown on an the alkaline, sandy and poor soil than on peat substrate, such demonstrating that SSADs have a fertilizing effect for plants growing on this kind of soil.